Strategi Pengimplementasian Konsep Kampung Tematik sebagai Wujud Masyarakat untuk Mengentaskan Desa 3T (Studi kasus: Kampung Tematik Kecamatan Kademangan Kota Probolinggo) - Meliana Putri; Husni Mubaroq (Inovbook, 2022)
The thematic village as an effort to preserve the Arts and Culture of the area in Kademangan ravine, is the title of this writing. Against the background of the condition of the community that has artistic and cultural potential but has not been nurtured to the maximum that has encouraged this writing. The method used is direct observation to the location of the Kademangan hamlet and direct interviews with people who know the existence of arts and culture in the Blimbing Gorge. From this study, it was found that the formation of thematic villages was needed as an effort to preserve the art and culture of the community. Especially in the Kademangan hamlet, the establishment of thematic arts and culture villages is very useful for the continuity of the arts and culture that exist in the community, especially the art of kuda lumping, kethoprak and calligraphy. So far, the three have already been in the community but have not been fully developed so that their existence is feared that they will gradually disappear if we do not preserve them. The formation of thematic villages is very important to support the preservation of Arts and Culture as well as being able to increase community income.